2015
DOI: 10.3109/02713683.2015.1008641
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Dysthyroid Optic Neuropathy: Long-Term Visual Outcomes with Comparison of 2-Wall versus 3-Wall Orbital Decompression

Abstract: Both 2-and 3-wall orbital decompressions are safe and effective for management of visual dysfunction in DON. Although 3-wall decompression provide better improvement in the parameters of visual field analysis and Hertel measures, new onset diplopia, adnexal/orbital complications are more common with this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Visual field defects of DON patients usually have various symptoms but are generally manifested as central scotoma, which can extend to the peripheral area as the disease develops, have different shapes, and be partially ameliorated after effective treatment. Previous studies have shown that decompression surgery can significantly increase the MD value with an average increase of approximately 9.4 to 10.0 dB [35,36]. is study revealed that the MD in operated eyes of DON patients improved more significantly than that in the fellow eyes received MPT alone, as also observed in the previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…Visual field defects of DON patients usually have various symptoms but are generally manifested as central scotoma, which can extend to the peripheral area as the disease develops, have different shapes, and be partially ameliorated after effective treatment. Previous studies have shown that decompression surgery can significantly increase the MD value with an average increase of approximately 9.4 to 10.0 dB [35,36]. is study revealed that the MD in operated eyes of DON patients improved more significantly than that in the fellow eyes received MPT alone, as also observed in the previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…Many authors recommend decompression of the medial wall as the best approach for patients with DON [8,9,19]. However, other surgical approaches are also presented: two-wall medial-lateral and three-wall medial-lateral-inferior orbital decompression combined with fat removal [20]. Due to such advantages as good visualisation of the orbital apex, the short time of hospitalisation, and lack of external scars, we performed EIODM.…”
Section: Discussionmentioning
confidence: 99%
“…A minority of these patients are at risk for hypophasis and corneal disorders. 3 Considering these factors, ICL surgery may be a better option for myopia patients with GO.…”
Section: Introductionmentioning
confidence: 99%